2020
DOI: 10.1016/j.nlm.2020.107267
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic/central coupling benefits working memory in healthy young adults

Abstract: Working memory (WM) is an executive function that can improve with training. However, the precise mechanism for this improvement is not known. Studies have shown greater WM gains after a period of sleep than a similar period of wake (Kuriyama et al. 2008a;Zinke, Noack, and Born 2018), with WM improvement correlated with slow wave activity (SWA; 0.5-1Hz) during slow wave sleep (SWS) (Sattari et al. 2019;Pugin et al. 2015;Ferrarelli et al. 2019). A different body of literature has suggested an important role for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 68 publications
(80 reference statements)
3
23
0
Order By: Relevance
“…43,44 Consistent with previous studies, BHI can describe certain cognitive states, which cannot be explained by changes in cardiac parameters by themselves. 15,21,45,46 In particular, the relationship between heartbeat dynamics and theta band was previously described in the resting state, showing that heartbeats may induce theta synchronizations in defined brain networks. 47 In this study, we showed that the theta band is actively modulated by vagal inputs under emotion elicitation.…”
Section: Discussionmentioning
confidence: 78%
“…43,44 Consistent with previous studies, BHI can describe certain cognitive states, which cannot be explained by changes in cardiac parameters by themselves. 15,21,45,46 In particular, the relationship between heartbeat dynamics and theta band was previously described in the resting state, showing that heartbeats may induce theta synchronizations in defined brain networks. 47 In this study, we showed that the theta band is actively modulated by vagal inputs under emotion elicitation.…”
Section: Discussionmentioning
confidence: 78%
“…In younger adults, daytime naps present with similar cardiac autonomic profiles as nighttime sleep (Cellini et al., 2016; Whitehurst et al., 2018), suggesting that daytime sleep too, serves a restorative function. These circadian‐ and sleep‐dependent shifts in the ANS are critical to the maintenance of autonomic balance between parasympathetic and sympathetic branches (Boudreau et al., 2013) and are beneficial for health and cognition (Chen et al., 2020a, 2020b; Thayer et al, 2009; Whitehurst et al., 2016, 2020). As we age, ANS functions can become more rigid, with decreased β‐adrenoreceptor response, decreases in baroreflex activity, diminished heart rate responses to acetylcholine, and decreases in cardiac parasympathetic activity (Chadda et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies have shown that fronto-parietal SOs, but not sigma, predicts WM improvement [31, 32]. However, not all studies report a consistent association between SOs and WM [3335], and few accounts for autonomic activity. Chen and colleagues reported that vagal activity during SWS was a better predictor of WM improvement than SWA or vagal activity during wake [15].…”
Section: Discussionmentioning
confidence: 99%